(untitled) (Journal of Advanced Research in Social Sciences, 2025)
This study examines the relationship between rates of reported violent crime and public institutional enrollment in postsecondary education between 1980 and 2020 in the United States. Focusing on violent crimes such as aggravated assault, forcible rape, and homicide, this research employs descriptive statistics, bivariate correlations, and regression analysis to examine the influence of rates of reported violent crime on public institutional enrollment in postsecondary education. The findings reveal a significant positive relationship between violent crime and public institutional enrollment, with forcible rape demonstrating a significant impact. These results challenge the hypothesis that higher crime rates prevent enrollment in postsecondary education suggesting instead that the rates of reported violent crime could be associated with increased student enrollment in public institutions. This research contributes to ongoing debates about the impact of reported violent crime on institutional enrollment in postsecondary education.